Successful coil embolization of post-hepatectomy arterioportal fistula that reduced ascites and improved liver function - Ryuta Okuhira, MD; Tetsuo Sonomura, MD, PhD; Ryota Tanaka, MD, PhD; Riki Inagaki, MD; Shota Ueda, MD, PhD; Kodai Fukuda, MD; Nobuyuki Higashino, MD; Atsufumi Kamisako, MD, PhD; Hirotatsu Sato, MD, PhD; Akira Ikoma, MD, PhD; Hiroki Minamiguchi, MD, PhD (Radiology Case Reports, 2024)
A 71-year-old man had previously undergone S7 + S8 dorsal segmentectomy and S5 partial hepatectomy for hepatocellular carcinomas. Six months later, he experienced abdominal distention. Abdominal computed tomography (CT) showed massive ascites and a significant hepatic arterioportal shunt. The ascites was thought to be caused by portal hypertension due to a high-flow hepatic arterioportal fistula (HAPF). The fistula, located between the right hepatic artery A7 and the right portal vein, was embolized with microcoils under flow control using a balloon catheter. After embolization, the shunt blood flow disappeared and the hepatopetal venous flow was restored. His body weight and abdominal circumference decreased immediately, and his liver function on blood tests improved after the procedure. CT performed 11 days after embolization showed decreased ascites. A HAPF after hepatectomy is extremely rare. Balloon-assisted embolization using microcoils is a useful endovascular procedure for treating a high-flow HAPF.